Intended Kurikulum Dan Implemented Kurikulum Dalam Pembelajaran Pendidikan Agama Islam - Resti Maharani Putri, Naila Nur Fatihah, Zahra Ramadini, Abdurrahmansyah (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study aims to analyze the implementation of the Islamic education curriculum in improving the quality of the learning process in educational institutions. Curriculum is an essential component in the education system that functions as a guideline for the implementation of teaching and learning activities. In the context of Islamic education, the curriculum does not only focus on knowledge mastery but also emphasizes character building and the development of students’ spiritual values. The research method used in this study is a qualitative approach with data collection techniques through literature study and analysis of various relevant scientific sources. The findings indicate that the effective implementation of the Islamic education curriculum requires synergy between curriculum planning, teacher competence, innovative learning strategies, and a supportive educational environment. Furthermore, the integration of Islamic values in the learning process plays a crucial role in shaping students’ noble character. Therefore, the development and implementation of the Islamic education curriculum must be carried out systematically and continuously to respond to the challenges of the modern era and the needs of society